Determination of the scientific name of tapeti (Lagomorpha: Leporidae) from the Pantanal - Cordeiro-Estrela, Pedro (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2022)
The tapeti is the only native South American lagomorph, all of which belong to the genus Sylvilagus, having 20 species distributed across central Mexico to Northern Argentina. A single species, Sylvilagus brasiliensis, and 22 subspecies previously recognized in the Neotropics have given way to many currently recognized species based on molecular, cytogenetic, and morphological data, three of which occur in Brazil. Sylvilagus brasiliensis sensu strcito was geographically restricted to the Pernambuco Endemism Center, the Atlantic Forest biogeographical region north of the São Francisco River. We propose that the Pantanal Sylvilagus species be given the name Sylvilagus brasiliensis sensu lato, based on significant cranial morphological differences with S. minensis, and in the absence of data from Pantanal specimens or specimens identified as S. paraguensis.
Keywords: Sylvilagus paraguensis; Sylvilagus minensis; Sylvilagus skull; Tapiti; Nhecolândia; Lagomorpha